(3WHbGJ GdabgGA GdTGaYjIs - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3hUdi Gddg Ydi eMeO NGJe GdfHjjf hHYO aEf GdTGaYi QVi Gddg Yfg bO MUd dg ai CUMGHg ef GdSYGOI CehQ de JJab ai CUMGH ZjQg s
(3BNQgG (B:s
(3GHh HcQ Hf LHQjd cGf PG Ydhe eJYOOI CeGekG ai Gdabg hGdCUdjf hQHeG cKjQ GdYHGOI hGdeQGbHI eGJ HRHjO SfI GMOi s
(3GdfSNI HgG MhGTs
(3HChdg Jedcs
(3HgG HYV GdChQGb HNW MOjKs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B119 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B203s
Keywords: (3GdJGQjNs